Electrocaloric and energy storage properties of sol-gel derived lanthanum doped PZT thick films. (1st November 2022) - Vandana,; Gupta, Reema; Tandon, Ram Pal; Tomar, Monika
Abstract: Electrocaloric effect has been investigated in lanthanum doped lead zirconium titanate (PLZT) thick films for potential application in cooling devices. Modified sol gel technique has been used for the preparation of PLZT thick films. Dielectric constant has been enhanced from 497 to 1048 with minimum dielectric losses varying from 0.04 to 0.07 measured at 1 MHz with increase in La doping from 2% to 6%, respectively. The maximum and remnant polarizations have been observed to vary from 23 μC/cm 2 to 62 μC/cm 2 and from 18 μC/cm 2 to 49 μC/cm 2 with increase in the lanthanum doping level from 2% to 6%, respectively, measured at 20 Hz frequency. The recoverable energy storage density of 1.05 J/cm 3 and an efficiency of 21% has been obtained for 2% lanthanum doping. The electrocaloric temperature change (ΔT) of 4.26K has been measured at 310K with an electrocaloric efficiency of 0.28 × 10 −6  Km/V in the 6% La doped PZT film. These properties indicate that PZT thick films with 6% La doping have potential for application in cooling devices.